(untitled) (Research, Society and Development, 2021)
Selaginella convoluta (Arn.) Spring, popularly known as jericho, resurrection plant, frog-hand, closed-hand or parrot-foot, is a species native to the flora of the Caatinga biome that is popularly used for therapeutic purposes. The aim of this study is to discuss the medicinal potentials of jericho (S. convoluta) in Northeastern popular medicine, describing its properties and main uses by the population. This is a descriptive, exploratory study of a qualitative nature, of the literature review type, which used 15 works of experimental and exploratory characteristics as a reference for the conduct of this research, found in the Scholar Google database, through the search with the following terms: "Selaginella convoluta caatinga", "jericó Selaginella convoluta", "Selaginella convoluta", "Selaginella convoluta medicina", "Selaginella convoluta etnobotânica", "Selaginella convoluta plantas medicinais" and "Selaginella convoluta comunidade". The data were organized in tables and tables in the Microsoft Excel 365 program. The results found in the literature suggest that jericho is used mainly as an antidepressant, diuretic, aphrodisiac, treat cough, dyslipidemia, amenorrhea, circulatory problems, anti-hemorrhagic, increase of female fertility, analgesic and anti-inflammatory, for having antioxidant, antimicrobial, antifungal and antinociceptive properties, due to the presence of its secondary metabolites, being consumed in the forms of teas, syrups and infusions. Therefore, Selaginella convoluta is evidenced as a herbal medicine that has many applications in medicine, for the relief, treatment and cure of diseases that affect the semiarid. It is also worth noting the need for further studies and publications with the species, since it can be very useful for the population.